A quantitative model for metabolic intervention using gut microbes. (16th January 2021) - Mays, Zachary J. S.; Nair, Nikhil U.
Abstract: As medicine shifts toward precision‐based and personalized therapeutics, utilizing more complex biomolecules to treat increasingly difficult and rare conditions, microorganisms provide an avenue for realizing the production and processing necessary for novel drug pipelines. More so, probiotic microbes can be co‐opted to deliver therapeutics by oral administration as living drugs, able to survive and safely transit the digestive tract. As living therapeutics are in their nascency, traditional pharmacokinetic–pharmacodynamic (PK–PD) models for evaluating drug candidates are not appropriate for this novel platform. Using a living therapeutic in late‐stage clinical development for phenylketonuria (PKU) as a case study, we adapt traditional oral drug delivery models to properly evaluate and inform the engineering of living therapeutics. We develop the a dapted for l iving t herapeutics c ompartmental a bsorption and t ransit (ALT‐CAT) model to provide metrics for drug efficacy across nine age groups of PKU patients and evaluate model parameters that are influenced by patient physiology, microbe selection and therapeutic production, and dosing formulations. In particular, the ALT‐CAT model describes the mathematical framework to model the behavior of orally delivered engineered bacteria that act as living therapeutics by adapting similar methods that have been developed and widely‐used for small molecular drug delivery and absorption.